Land use and Land cover maps and the remadation of sand dune movements in Salahaddin Governorate - Sadoon, Hala; Adnan, Ghader; Majed, Maitham (Iraqi Journal of Science, 2024)
Landsat were used to constract Land use and Land cover maps for some district in Salahaddin Governorate by using ERDAS Imagine for Supervised Classification.